Consequences of Paleosubduction Regime for Geochemical Prospecting and Prospectivity of Coromandel Peninsula, New Zealand (The Australasian Institute of Mining and Metallurgy, 1987)
A tectonic interpretation of the Coromandel Peninsula which suggests that the basement underwent tensional collapse at its northern and southern ends would permit more ready penetration of late stage magmatic fluids. This hypothesis is consistent with regional trends of the chloride content of low grade geothermal waters and of the yield of gold and silver per unit weight of quartz worked. The consequences of such a model are that mercury should not only be a good pathfinder for Coromandel gold, but that it should be correlative with ratios of base metals high in the zoning or paragenetic sequences to those lower in the sequences. This is demonstrated successfully in an area of mineralisation in the southern Coromandel.